Traditional Chinese medicine trade among RCEP countries: structural characteristics and determinants - Fang, Yue; Tang, Meng Xue; Liu, Xu (Frontiers in Public Health, 2025)
BackgroundWith the increasing global focus on health and the growing popularity of natural therapies, Traditional Chinese Medicine (TCM) products, including extracts, crude drugs, and herbal preparations, are widely utilized as both primary and complementary medicines worldwide. The Regional Comprehensive Economic Partnership (RCEP), spanning 15 countries across East Asia, Southeast Asia, and Oceania, offers a vast market for TCM. However, limited research has been conducted on the complex trade relations among RCEP members.MethodsThe structural features and nodes attributes are analyzed using Social Network Analysis (SNA). Influencing factors are studied through the Quadratic Assignment Procedure (QAP) model. We also compiled a list of medicinal plants among RCEP member countries and the main TCM export products.ResultsThe scale of TCM trade among RCEP members has fluctuated over time, with a temporary spike during the COVID-19 pandemic, followed by a gradual normalization. The trade network does not exhibit small-world properties, indicating a relatively balanced trade relationship. Due to its resource advantages, China occupies a central role acting as a dominant producer and leading exporter. Vietnam’s export performance has been excellent in recent years, with the highest annual growth rate. Emerging markets, such as Myanmar, warrant closer attention. Economic size and population significantly positively affect trade value, while geographic distance and land adjacency have no significant impact. Trade activity is positively influenced by cultural and linguistic similarities, and countries with higher levels of economic freedom tend to engage in more trade. Tonifying TCM products with antioxidant and immune-boosting properties are more widely recognized in international markets.ConclusionRCEP has established an excellent trade platform for the export of TCM. The factors influencing TCM trade are predominantly long-term and structural, rather than being driven by the occurrence of any single, isolated event. Member states should strengthen collaboration in standardization, technology coordination, and knowledge sharing to establish a mutually beneficial trade ecosystem for TCM.